Причини возникновения синдрома эмоционального выгорания у врачей-хирургов = Causes burnout syndrome have surgeon - Aymedov, K. V. (Journal of Education, Health and Sport, 2015)
Aymedov K. V. Причини возникновения синдрома эмоционального выгорания у врачей-хирургов = Causes burnout syndrome have surgeon. Journal of Education, Health and Sport. 2015;5(4):273-277. ISSN 2391-8306. DOI: 10.5281/zenodo.16938 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A273-277 http://dx.doi.org/10.5281/zenodo.16938 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. УДК 159. 942.5: 37.01 ПРИЧИНИ ВОЗНИКНОВЕНИЯ СИНДРОМА ЭМОЦИОНАЛЬНОГО ВЫГОРАНИЯ У ВРАЧЕЙ-ХИРУРГОВ CAUSES BURNOUT SYNDROME HAVE SURGEON К. В. Аймедов K. V. Aymedov Одесский национальный медицинский университет, Украина Odessa National Medical University, Ukraine Abstract The article presents the problems of emergence doctor’s surgical professional burnout syndrome. We present the main components of emotional burnout syndrome among physicians with different experience of professional activity. At the bottom of the article, based on the assumption that the risk of reactive formations and deviations will grow in line with increasing the duration of the work in the environment stress level factors. Revealed that the high workload duty on weekends, increasing the number of patients, insufficient provision of hospitals, lack of moral and material compensation for the work and other factors cause negative emotions doctors. All this leads to dissatisfaction with their profession. Key words: burn-out syndrome, surgeons, emotional exhaustion. Резюме В статье раскрываются проблемы возникновения синдрома эмоционального выгорания у врачей хирургического профиля. Приведены основные компоненты синдрома психического выгорания у врачей с разным стажем профессиональной деятельности. В основании статьи, лежит предположение, что риск развития реактивных образований и девиаций будет расти в соответствии с увеличением длительности роботы в среде стресогенных факторов. Выявлено, что высокая рабочая нагрузка, дежурства в выходные дни, увеличение количества пациентов на одного врача, недостаточное обеспечение больниц, недостаточное моральное и материальное вознаграждение за работу и другие факторы вызывают негативные эмоции у врачей. Все это приводит к неудовлетворенности своей профессией. Ключевые слова: синдром эмоционального выгорания, врачи-хирурги, эмоциональное истощение.